Combining food web theory and population dynamics to assess the impact of invasive species - Vagnon, Chloé; Rohr, Rudolf P.; Bersier, Louis-Félix; Cattanéo, Franck; Guillard, Jean; Frossard, Victor (Frontiers in Ecology and Evolution, 2022)
The impacts of invasive species on resident communities are driven by a tangle of ecological interactions difficult to quantify empirically. Combining a niche model with a population dynamic model, both allometrically parametrized, may represent a consistent framework to investigate invasive species impacts on resident communities in a food web context when empirical data are scarce. We used this framework to assess the ecological consequences of an invasive apex predator (Silurus glanis) in peri-Alpine lake food webs. Both increases and decreases of resident species abundances were highlighted and differed when accounting for different S. glanis body sizes. Complementarily, the prominence of indirect effects, such as trophic cascades, suggested that common approaches may only capture a restricted fraction of invasion consequences through direct predation or competition. By leveraging widely available biodiversity data, our approach may provide relevant insights for a comprehensive assessment and management of invasive species impacts on aquatic ecosystems.